Global Peace: A Dream Yet to Be Realized Hayab John Joseph- Director, Global Peace Foundation, Nigeria - Joseph, Hayab John (International Journal of Advanced Research in Peace, Harmony and Education, 2024)
Global peace, a timeless aspiration of humanity, remains elusive amidst the complexities of the modern world. This paper aims to explore the multifaceted nature of global peace, drawing on theoretical frameworks, practical approaches, and persistent challenges. Theoretical perspectives such as the democratic peace theory and economic interdependence theory shed light on the conditions conducive to peace. The democratic peace theory, championed by scholars like Michael Barnett, posits that democracies exhibit a decreased propensity to engage in warfare with one another. This inclination is attributed to a confluence of factors including shared democratic values, a commitment to human rights, and the presence of well-established mechanisms for peaceful conflict resolution. Democracies, characterized by their emphasis on dialogue, negotiation, and compromise, are perceived as less prone to resorting to violence in resolving disputes, thereby fostering a more peaceful international environment. Similarly, economic interdependence theory, elucidated by Bruce Russett and John Oneal, argues that the deepening interconnections of trade and economic ties between nations serve as effective deterrents for the outbreak of war. According to this theory, as countries become increasingly intertwined economically, they become mutually dependent on each other’s prosperity. In the event of armed conflict, the disruption to economic interdependence would result in mutual economic harm, thereby dissuading nations from resorting to war. This theory underscores the pragmatic economic benefits of peace, incentivizing states to prioritize diplomatic resolutions and peaceful cooperation over belligerent actions. International institutions like the United Nations (UN) and regional organizations play crucial roles in peacebuilding and conflict resolution. However, achieving sustainable peace requires addressing root causes of conflict, including poverty, inequality, resource scarcity, and ethnic tensions. Moreover, emerging challenges such as terrorism, weapon proliferation, climate change, and pandemics pose new threats to global security. Despite these challenges, investing in diplomacy, conflict prevention, education, and sustainable development offers pathways towards a more peaceful future. By understanding the complexities of global peace and pursuing collaborative efforts, humanity can inch closer to realizing the dream of a world where peace prevails.